IMPLEMENTASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI DI KEMENTERIAN AGAMA KOTA LHOKSEUMAWE - Hafni, Nur; Mardhiah, Ainol; Abu Bakar, Muhammad Bin; Fakhrurrazi, Fakhrurrazi (FISIP Universitas Malikussaleh, 2025)
This research examines the implementation of the Integrated Dynamic Archival Information System (SRIKANDI) at the Ministry of Religious Affairs Office of Lhokseumawe City. SRIKANDI, mandated since December 1, 2022, by the Circular Letter of the Secretary General of the Ministry of Religious Affairs No. 31 of 2022, aims to support the Electronic-Based Government System (SPBE) by enhancing transparency, accountability, and efficiency in archival management. However, initial observations indicate that the implementation of this application is not yet optimal, with many archives still managed conventionally. This research aims to: 1) analyze the implementation of SRIKANDI at the Ministry of Religious Affairs Office of Lhokseumawe City, 2) identify obstacles in its implementation, and 3) evaluate efforts made to overcome these obstacles. The method used is descriptive qualitative analysis, with data collected through interviews, observations, and documentation. The research informants consist of Civil Service Apparatus (ASN) employees and SRIKANDI operators within the Ministry of Religious Affairs Office of Lhokseumawe City. The results show that the implementation of SRIKANDI faces several obstacles, including low understanding and skills of employees in using the application, lack of direction and socialization from leadership, limited facilities and infrastructure, and poor coordination between work units. Nevertheless, the Ministry of Religious Affairs Office of Lhokseumawe City has shown a commitment to overcoming these obstacles through increased training, the formation of special teams, and the provision of adequate facilities. In conclusion, despite various barriers in the implementation of SRIKANDI, continuous improvement efforts are being made to achieve more efficient and transparent archival management, supporting the overall implementation of SPBE.